جنُوح الأحداث دراسة مقارنة بين ال ّشريعة الإسلاميّة والتّشريع الجزائري - عزوزة, أسماء (University of eloued جامعة الوادي, 2015)
تناولت ىذه الّدراسة ظاىرة ُجنوح الأحداث من المنظُور الإسلامي وكذا التّشريع الجزائري، وتمّ التّطّرق فيها إلى مفهوم ُجنوح الأحداث وكذا العوامل الدؤّدية لذذا الجُنوح، بالإضافة إلى الأساس الذي تقوم عليو مسؤولية الأحداث الجنائيّة، ومراحل تدّرج ىذه الدسؤوليّة، وتم الترّكيز في ىذه الّدراسة على الحماية الجنائيّة للأحداث الجانحين، حي ُث َوقَْف ُت على أى ّم ال ّضمانات الّتّ َكَفلتها ال ّشريعة الإسلاميّة والتّشريع الجزائري لفئة الأحداث الجانحين في جميع مراحل الّدعوى خا ّصة مرحلتّ التّحقيق والدُحاكمة، وكيف تميّزت إجراءات ُمُاكمتِهم عن الإجراءات الخا ّصة بالدُ ْجِرمين البالغين، وَختَم ُت ىذه الّدراسة بمجموعة من الأساليب والأُ ُسس التّ سطَّرتهاكل من الشريعة الإسلامية والتّشريع الجزائري، التّ من شأنها أن تَُوا ِجو أو على الأق ّل تُقلّل من ظاىرة الجُنُوح. This study dolt with the phenomenon of criminal children from an Islamic and Algerian legislation point of view during this study‚ it’s dolt with the definition of criminal children and the causes that lead to these crimes‚ beside to the responsibility of the criminal events and the steps of this responsibility‚ In this study‚ it’s focused on the penal protection for those criminal children as it concentrated on the main guarantee that was assumed by the Islamic code of laws and the Algerian legislation for those criminal children in all steps of the law suit especially the two main steps which are the investigation and the trial and how the measures of their trial is distinguished from the criminal adults‚ this study ends by many ways and basic principles which are put by Islamic code of laws and the Algerian legislation aiming to fare this phenomenon of criminal children or at least to decrease it
شريعة وقانون
Keywords: جنُوح/ الأحداث/التّشريع الجزائري; Delinquency/ Juveniles/ Algerian Legislation